2019
DOI: 10.1007/s42235-019-0106-4
|View full text |Cite
|
Sign up to set email alerts
|

Bionic Flapping Pectoral Fin with Controllable Spatial Deformation

Abstract: This paper presents the biomimetic design of a bionic pectoral fin with fin rays driven by multi-joint mechanism. Inspired by the cownose ray, the bionic pectoral fin is modeled and simplified based on the key structure and movement parameters of the cownose ray's pectoral fin. A novel bionic propulsion fin ray composed of a synchronous belt mechanism and a slider-rocker mechanism is designed and optimized in order to minimize the movement errors between the designed fin rays and the spanwise curves observed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…However, discrepancies arise for efficiency. This difference is reconciled by a study on cownose ray pectoral fin performance where both efficiency and thrust are reported to increase with higher bending angles [ 40 ]. The geometry and kinematics of the cownose ray model more closely match those used in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…However, discrepancies arise for efficiency. This difference is reconciled by a study on cownose ray pectoral fin performance where both efficiency and thrust are reported to increase with higher bending angles [ 40 ]. The geometry and kinematics of the cownose ray model more closely match those used in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Triantafyllou [16] found that an oscillating foil at the frequencies of maximum spatial amplification could achieve optimal propulsion for St (Strouhal number) values in the range of 0.25 to 0.35. Bi and Cai [17][18][19][20] conducted several hydrodynamic experiments and showed that both the thrust coefficient and efficiency reached the maximum at St = 0.4, the most flexible tailplane had the highest propulsive efficiency, and the Reynolds number had a significant effect on the propulsive efficiency. Michelin [21] investigated the effect of the bending stiffness of a flexible heave wing on its propulsion performance in twodimensional imposed parallel flow in the inviscid limit, and they found that flapping efficiency is greatly enhanced by flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…These studies are much useful for the design and further research of bio-inspired autonomous underwater vehicles (BAUVs). Scientists have created different kinds of manta robots and have been trying to enhance their propulsion [8][9][10][11][12][13]. Cai et al [10] conducted a large number of hydrodynamic experiments and pectoral fin swing propulsion designs of caw-nosed manta rays.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have created different kinds of manta robots and have been trying to enhance their propulsion [8][9][10][11][12][13]. Cai et al [10] conducted a large number of hydrodynamic experiments and pectoral fin swing propulsion designs of caw-nosed manta rays. The well-known B-2 stealth and strategic bomber of the US military is the most successful example of a manta ray biomimetic aircraft [14].…”
Section: Introductionmentioning
confidence: 99%